ANALISIS PENGARUH ASPEK KEPERILAKUAN TERHADAP SISTEM AKUNTANSI (STUDI KASUS PADA PT. SINAR GALESONG PRIMA DI MANADO) - Mogontha, Wulan; Nangoi, Grace B.; Gerungai, Natalia (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
Accounting is information or, to be specific, accounting system. AccountingÂ System has important role in a company where the success of an accounting system depends on the human behavior as respond giving user. Therefore, there should be a necessary consideration regarding behavioral aspect in running an accounting system whereas be behavioral accounting is focusing on accountantâs and auditorâs decision making wether the system is run according to the companyâs procedure and their objective as well. This research is aimed to analize the effect of behavioral aspect on accounting system run by PT Sinar Galesong Prima in Manado as a trading company. The method of analysis applied is multiple linear regression. The result of the conducted research shows that behavioral aspect (Attitude, Motivation, Perseption, Emotion) is not significantly affected the accounting system run by the company. It is expected that the company would give more concern, particularly to the behavioral aspect in applying the existing system so that in the future, the accounting system in the company could run effectively and efficiently according to the companyâs objective.Keywords : Accounting System, Behavioral Accounting, Attitude, Motivation, Perpseption, Emotion.